Primary Glioblastoma with Different Patterns of EGFR Amplification and the Relationship with Gene Expression Profile - Lopez-Gines, Concha; Gil-Benso, Rosario; Monleon, Daniel; Gonzalez-Darder, Jose; Cerda-Nicolas, Miguel (IntechOpen, 2011)
None